1989
DOI: 10.1016/0014-5793(89)80504-6
|View full text |Cite
|
Sign up to set email alerts
|

myo‐Inositol 1,4,5‐trisphosphorothioate is a potent competitive inhibitor of human erythrocyte 5‐phosphatase

Abstract: The effect of the myo-inositol 1,4,5-trisphosphate (IP,) analogue, myo-inositol 1,4&trisphosphorothioate (IPS,) on the dephosphorylation of D-S-f2P]IP, by the 5-phosphatase from human erythrocyte membranes has been investigated. DL-IP& was found to act as a competitive inhibitor with a Ki of 6 pM, making it the most potent inhibitor currently available for this enzyme. LIP, inhibited the enzyme with a Ki of 124 gM and was more potent than D-2,3_diphosphoglycerate(Ki 978 PM).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2001
2001

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 17 publications
(10 reference statements)
0
19
0
Order By: Relevance
“…2,3 DPG in these cases evoked a small transient response, but again Finally, the phosphatase-resistant analogue DLinositol 1,4,5-trisphosphorothioate (Ins 1,4,5 P(S)3) was used (Cooke et al, 1987;Hamblin, Flora & Potter, 1987;Taylor et al, 1988). This analogue, as well as being a potent releaser of calcium, is a much more effective 5-phosphatase inhibitor than 2,3 DPG and has a Ki of 6 /,ZM (Cooke, Nahorski & Potter, 1989). Ins 1,4,5 P(S)3 (100 btM, corresponding to 50 >M of the D-form) evoked a transient response very similar to that seen when using Ins 1,4,5 P3 (Fig.…”
Section: Is the Transient Response To Ins 145 P3 Stimulation Due Tomentioning
confidence: 98%
“…2,3 DPG in these cases evoked a small transient response, but again Finally, the phosphatase-resistant analogue DLinositol 1,4,5-trisphosphorothioate (Ins 1,4,5 P(S)3) was used (Cooke et al, 1987;Hamblin, Flora & Potter, 1987;Taylor et al, 1988). This analogue, as well as being a potent releaser of calcium, is a much more effective 5-phosphatase inhibitor than 2,3 DPG and has a Ki of 6 /,ZM (Cooke, Nahorski & Potter, 1989). Ins 1,4,5 P(S)3 (100 btM, corresponding to 50 >M of the D-form) evoked a transient response very similar to that seen when using Ins 1,4,5 P3 (Fig.…”
Section: Is the Transient Response To Ins 145 P3 Stimulation Due Tomentioning
confidence: 98%
“…5 demonstrate that the 3-kinase-insensitive 3-¯uoro analog of Ins(1,4,5)P 3 causes Ca 2+ release in stamen hair cells and is quickly inactivated, consistent with the absence of reports of Ins(1,4,5)P 3 3-kinase activity in plant cells. By contrast, when the 5-monophosphothioate analog of Ins(1,4,5)P 3 (Cooke et al 1989;Safrany et al 1991) was injected, a sustained elevation of [Ca 2+ ] was observed (Fig. 6), with little or no inactivation over the course of measurement.…”
Section: Discussionmentioning
confidence: 77%
“…i)i.-InsP,-SS is phosphorylated by this enzyme with a 'K5,,' similar to Ins( 1,4,S)P,; in contrast, i)i,-Ins ( 1,4,5)PS3 interacts only weakly with this enzyme and inhibits activity. This difference is likely to be due to the presence of the 4-phosphorothioate group in i)i,-Ins ( 1,4,5)pS3, which may disrupt the required orientation of the 3-hydroxyl group or interfere with access of the cosubstrate ATP to the 3-kinase active site [43,441. It is also noteworthy that total phosphorothioate substitution, in addition to making the analogue metabolism-resistant, also increases the potency of 5-phosphatase inhibition [43,441, and it is a matter of priority to establish whether the [,-isomer of inositol trisphosphorothioate ([,-Ins( 1,4,5)PS3) exhibits sufficient selectivity for the 5-phosphatase relative to other recognition sites to allow truly specific 5-phosphatase inhibition in cellular systems.…”
Section: Volume 19mentioning
confidence: 98%